Place of derivative adjectives with suffixes -ьн- and -ьск- in the Old Russian language (based on chronicles material) - Yerofeeva, Irina (Przegląd Wschodnioeuropejski, 2018)
The article studies functional and semantic peculiarities of derivative adjectives with suffixes -ьн- and -ьск- from chronicles. The character of substantival adjectival syntagmas being the main unit of Old Russian texts has been analyzed. Reference field of different characteristics which are important for medieval languages has been revealed. Spheres of functioning of two sets of the most productive suffixes have been defined. These are sets which take part in formation of characteristic culture space. Adjective units are researched with the help of semantic cognitive method in a functional and cultural perspectives. As a result lexical and grammatical semantics of adjectives ending in -ьн- and -ьск- in Old Russian have been revealed as well as the main groups of derivative bases, and most frequent syntagmas with these types of adjectives have been described.